Decolonizing perspectives of arts education - Rose Martin; Sunniva Skjøstad Hovde; Robert Chanunkha; Pauline Hiroti (Cappelen Damm Akademisk NOASP, 2021)
This special issue of JASEd offers insights to current research and practice pertaining to decolonizing perspectives of arts education. As the editors of this special issue, we each come from distinct positionalities, geographical locations, and contextual understandings. We found common ground in the need to discuss and share around the theme of decolonizing arts education. Spurred on by the seismic shifts of power, politics, and polarization that the world is currently experiencing, we noted an urgency to address what this might all mean in and for arts education.